Peran Klaster IKM Sentra Kerupuk Ikan Sei Lekop dalam Pembangunan Ekonomi - Ade Septiany; Ayu Wardani; Intan Putri Nurhayati; Laura Atalia; Maya Larasati; Reza Resmaliana; Vina Loreza (Institut Nalanda, 2023)
The growth of MSMEs is an important part of economic development and achieving goals in Indonesia. Currently, economic growth can continue to develop with the existence of SMEs which are one of the drivers and incentives for the economy in Indonesia which can be used as a support in helping the economic development of society in Indonesia for the sake of valuable social welfare. The aim of this research is to determine the role of SMEs in the national economy, especially government support for SMEs in increasing economic growth and employment. In this research, researchers used qualitative methods by conducting interviews, surveys and observations. The results of the research are that the government does not remain silent and just wait for the results of community efforts, but in this IKM the government also contributes directly to economic development and helps business actors in the fish cracker industry by providing contributions in terms of various assistance, of course, such as providing production houses accompanied by also with various equipment needed to manage fish crackers to help Fish Cracker SMEs to fulfill their needs as business actors by seeing an increase in the income they earn.